Decision Model for Medium-Term Municipal Waste Collection Optimisation - Paweł Hanczar (Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu)
Aim: The article presents the process of municipal waste management, with particular emphasis on the organization of waste collection, and discusses the objectives of waste management, the principles of operation in Poland and order in municipalities, and various approaches to organizing waste collection. The rest of the article presents a decision model for schedule generation based on mixed integer programming (MIP). This model aims to minimise the number of resources involved while meeting the requirements regarding the frequency of waste collection. One distinguishing characteristic of the proposed method is its premise that transport-related work should remain constant throughout the entire year, irrespective of holidays or days off. To achieve this, the model incorporates schedule substitutions which enable the strategic adjustment of schedules for collection dates affected by holidays, while preventing significant spikes in waste collection volume on those days.